Burden of large vessel occlusion stroke and the service gap of thrombectomy: A population-based study using a territory-wide public hospital system registry. Issue 1 (January 2020) - Tsang, Anderson C.O.; You, Jia; Li, Lai Fung; Tsang, Frederick C.P.; Woo, Pauline P.S.; Tsui, Eva L.H.; Yu, Philip; Leung, Gilberto K. K.
Background: Ischemic stroke due to large vessel occlusion can be effectively treated with thrombectomy but access to this treatment is limited in many parts of the world. Local incidence of large vessel occlusion is critical in determining the development of thrombectomy service, but reliable data from Asian countries are lacking. Aims: We performed a population-based study to estimate the burden of large vessel occlusion and the service gap for thrombectomy in Hong Kong. Methods: All acute ischemic stroke patients admitted in 2016 to the public healthcare system, which provided 90% of the emergency healthcare in the city, was identified from the Hong Kong Hospital Authority's central electronic database. The diagnosis of large vessel occlusion was retrospectively verified by two independent cerebrovascular specialists in a randomly sampled cohort based on clinical and neuroimaging data. The incidence of large vessel occlusion in the population was estimated through weighting the sample results and compared with the thrombectomy data in the same period. Results: There were 6859 acute ischemic stroke patients treated in the public health system in 2016. Amongst the 300 patients randomly sampled according to diagnosis coding, 130 suffered from anterior circulation large vessel occlusion. This translated to 918 patients (95% CI 653–1180) and 13.3% of all ischemic stroke patients. The estimated incidence of anterior circulation large vessel occlusion was 12.5 per 100, 000 persons per year (95% CI 11.7–13.4). Large vessel occlusion stroke patients were more commonly female than male (67.4% vs. 31.6%, p = 0.003), and were older than non-large vessel occlusion stroke patients (mean of 80.5 years vs. 71.4 years, p = < 0.001). They also had higher 30-day mortality rate (31.1% vs. 4.6%, p = < 0.001), and longer hospital stay (mean 38.6 vs. 21.1 days, p = 0.003) than non-large vessel occlusion stroke. In the same period, 83 thrombectomies for large vessel occlusion were performed, representing 9.1% of the estimated large vessel occlusion incidence. Conclusion: The estimated incidence of anterior circulation large vessel occlusion in the Hong Kong Chinese population is lower than that in the West. There is however a substantial service gap for endovascular thrombectomy with less than 10% of large vessel occlusion patients receiving thrombectomy.